Bully proofing your school : a comprehensive approach for elementary schools - Garrity, Carla (Sopris West, 2000)
A team of educators, psychologists and social workers in the Chery Creek Schools in Colorado have developed this comprehensive program designed to make the school environment safe for children both physically and psychologically.